Synthesis and Bioevaluation of Thieno[2,3-d]pyrimidinone Derivatives as Potential Tumor Cell Growth Inhibitors - Huangyong Li; Changshui Chen; Shengzhen Xu; Xiufang Cao (Journal of Chemistry)
A series of novel cycloalkylthieno[2,3-d]pyrimidinone derivatives have been conveniently synthesized via three steps including G-3CR, heterocyclization, and alkylation reactions as a part of our ongoing search for new bioactive molecules. The newly synthesized compounds were evaluated for their potential tumor cell growth inhibitory activity by standard MTT assay. The preliminary results show that compound 6b exhibited better inhibitory activities against HepG2, MCF-7, and BCG-823 cell lines compared to the control.